2018
DOI: 10.1186/s12909-018-1227-x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of learning factors in postgraduate health sciences master students: a comparative study with non-health science students and between genders

Abstract: BackgroundThe students’ conceptions of learning in postgraduate health science master studies are poorly understood. The aim of this study was to compare the factors influencing conceptions of learning in health sciences and non-health sciences students enrolled in postgraduate master programs in order to obtain information that may be useful for students and for future postgraduate programs.MethodsA modified version of the Learning Inventory Conception Questionnaire (COLI) was used to compare students’ concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
(40 reference statements)
2
5
0
2
Order By: Relevance
“…Significant differences were found only for the procedural component and for the “Biofabrication components for advanced therapies” topic, but not for the conceptual and attitudinal components. These findings are consistent with the patterns usually described in relation to gender and medicine [15, 4648]. Our results can contribute to a better understanding of residents’ profiles regarding advanced therapies, and the slight gender differences detected in our respondents should be taken into account when new training programs are implemented in this area.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Significant differences were found only for the procedural component and for the “Biofabrication components for advanced therapies” topic, but not for the conceptual and attitudinal components. These findings are consistent with the patterns usually described in relation to gender and medicine [15, 4648]. Our results can contribute to a better understanding of residents’ profiles regarding advanced therapies, and the slight gender differences detected in our respondents should be taken into account when new training programs are implemented in this area.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study we investigate different components of perception (e.g. conceptual, procedural and attitudinal) in family medicine residents in Spain in order to determine the variables or constructs which could serve as a foundation for their future learning processes in advanced therapies [15, 16]. These variables or constructs can be defined as the way in which students conceptualize and relate to the learning process, which is assumed to affect their learning and achievements [17].…”
Section: Introductionmentioning
confidence: 99%
“…Learning and gender: Interestingly, females were more likely to correctly answer knowledge questions in both pre‐ and post‐test scores. While there is a contradictory literature in this area (Al‐Saud, ; Campos et al, ), this is consistent with some research on gender learning in health which suggests that females demonstrate higher planning, task management and persistence, and that these may be mediating factors in terms of outcome (Edgar, ). However, there remains some consensus that the effect of gender on learning is poorly understood (Campos et al, ).…”
Section: Discussionsupporting
confidence: 80%
“…The finding that individuals with less than 5 years specialized early intervention experience performed better at post than those with more than 5 years is an interesting one. While a number of factors may explain this, potential mediators could be that motivation was potentially higher in younger students (Campos et al, ; Tsoiw et al, ), and that younger age participants (ie, aged 20‐29) have been found to demonstrate significantly higher scores in learning gains (Lim, Morris, & Yoon, )…”
Section: Discussionmentioning
confidence: 99%
“…Medical education is challenging as it must emphasise and lead to the acquisition of theoretical knowledge but also practical skills. For medical students from various cultural groups, gaining information is as important as learning to use, remember and understand it [1]. There is nowadays an increasing trend to move from a classical teacher-centered to a student-centered modality of teaching [2].…”
Section: Introductionmentioning
confidence: 99%